Neuronal NCX1 overexpression induces stroke resistance while knockout induces vulnerability via Akt. Issue 10 (October 2016) - Molinaro, Pasquale; Sirabella, Rossana; Pignataro, Giuseppe; Petrozziello, Tiziana; Secondo, Agnese; Boscia, Francesca; Vinciguerra, Antonio; Cuomo, Ornella; Philipson, Kenneth D; De Felice, Mario; Di Lauro, Roberto; Di Renzo, Gianfranco; et al.
Three different Na + /Ca 2+ exchanger (NCX) isoforms, NCX1, NCX2, and NCX3, are expressed in brain where they play a relevant role in maintaining Na + and Ca 2+ homeostasis. Although the neuroprotective roles of NCX2 and NCX3 in stroke have been elucidated, the relevance of NCX1 is still unknown because of embryonic lethality of its knocking-out, heart dysfunctions when it is overexpressed, and the lack of selectivity in currently available drugs. To overcome these limitations we generated two conditional genetically modified mice that upon tamoxifen administration showed a selective decrease or increase of NCX1 in cortical and hippocampal neurons. Interestingly, in cortex and hippocampus NCX1 overexpression increased, where NCX1 knock-out reduced, both exchanger activity and Akt1 phosphorylation, a neuronal survival signaling. More important, mice overexpressing NCX1 showed a reduced ischemic volume and an amelioration of focal and general deficits when subjected to transient middle cerebral artery occlusion. Conversely, NCX1-knock-out mice displayed a worsening of brain damage, focal and neurological deficits with a decrease in Akt phosphorylation. These results support the idea that NCX1 overexpression/activation may represent a feasible therapeutic opportunity in stroke intervention.